BAUSUNG PENGANTIN PADA MASYARAKAT BANJAR DALAM PERSPEKTIF HUKUM ISLAM - Muhammad Adib (Musyarokah: Jurnal Hukum dan Ekonomi Islam, 2025)
Bausung pengantin is the carrying of a bride and groom before they walk down the aisle (when the groom comes to the bride’s house). Bausung is performed by two dancers accompanied by Banjar music, the two dancers carry the bride and groom witnessed by the guests and invitees present towards the aisle. The bridal bausung tradition has been carried out by the indigenous Banjar people from generation to generation, but what is different for today is only the time of implementation which is now only done in the afternoon at the wedding ceremony. This journal aims to see how Islamic law views the tradition of bausung pengantin in the Banjar community. The research method in this journal is normative legal research using qualitative analysis. The research result of this journal is the permissibility of bausung pengantin as long as the practice is in line with Islamic law. However, if the practice contains elements of shirk or other immorality then this is prohibited in Islam.